Hong Kong Output Dynamics: An Empirical Analysis - Yin-Wong Cheung (Center for Economic Studies and ifo Institute (CESifo), 2001)
Advanced statistical techniques are used to analyze Hong Kong output dynamics. Hong Kong, Japan and the U.S. are found to share some common long-term and short-term cyclical variations. While the Hong Kong economy is susceptible to external shocks and Granger-caused by the other two economies, local factors account for a large proportion of output growth variability and are mainly responsible for her output uncertainty. On the transmission mechanism, the selected trade and financial variables have incremental explanatory power but do not lessen the ability of domestic and foreign output variables to explain Hong Kong growth dynamics. Interestingly, the U.S. does not appear to exert undue influences on Hong Kong.
Keywords: 330; Common trends/cycles; transmission mechanism; structural determinants